How Do Norwegian Technology Start-ups Use Open Innovation Strategies to Gain Access to New Business Ideas? - Rahman Minhazur (De Gruyter, 2021)
Open innovation (OI) strategy includes inter-company processes and activities i.e. networking, management, communication etc. The intention of this paper is to present examples on how open innovation performs within these start-ups. This paper is a descriptive study that discusses how to implement open innovation strategies in order to gain access to new business ideas in Norwegian tech companies. Throughout the study and analysis of appropriate literature, this research aims to deepen the understanding of the initial question and provide direction for further research. This improved understanding of using open innovation strategies will help entrepreneurs, as well as policy makers involved in idea evaluation. This study deals with the OI strategy implementation in small companies and startups, both of which are almost untouched fields of study. It contributes recommendations for reality thinking, social media involvement, and planned versus arbitrary strategy. This qualitative research paper forms a case study based on structured interviews with four anonymous Norwegian tech start-ups. Twenty to twenty-five articles about “startups, open innovation and networking” have been selected and analysed for the purpose of this paper. This study outlines a clear method for reviewing the theories of open innovation and networking which are discussed in the objectives. Unlike previous research, this paper will highlight loopholes and common mistakes typically made by start-ups and instead will implement smooth open innovation strategies for their company’s benefit. After conducting successful interviews with start-up, the results have been combined with literature reviews and related theories with empirical evidence to support the proposed question. Finally, the findings are categorised in the table below and organised according to interviewee answers.